MEMAHAMI ESENSI KOMUNIKASI ANTARPRIBADI DALAM PROSES TAARUF: STUDI PADA KADER WAHDAH ISLAMIYAH GORONTALO - Talalu, Taufik R; Tamu, Yowan; Sumarjo; Malik, Abdul (Farabi, 2023)
This research delves into the taaruf (Islamic courtship) process within the context of Wahdah Islamiyah Gorontalo, particularly among active members of the halaqoh (study circle) tarbiyah (spiritual development) group who choose their life partners through the taaruf method. Employing a qualitative approach, this study explores various relevant aspects of the taaruf process within the framework of Wahdah Islamiyah Gorontalo. It encompasses the examination of effective interpersonal communication characteristics outlined by DeVito, including openness, empathy, supportiveness, positivity, and equality. The analysis of these characteristics provides a deeper understanding of how effective communication influences the dynamics of the taaruf process within Islamic culture. This research reveals the significance of applying principles of effective communication to assist prospective partners in seeking marital unions based on good intentions, understanding, support, and fairness within the taaruf process.